Model Teams Games Tournament (TGT) dalam Meningkatkan Hasil Belajar Siswa Sekolah Dasar - Hesti, Retta Chandra; Murdiyah, Sri; Suminah, Suminah (Universitas Negeri Malang, 2019)
The observation results at Melis Elementary School in Trenggalek Regency showed that students were less enthusiastic in learning because the use of learning models was less attractive, of which 17 students stated 11 were not yet complete, and 6 were complete. The purpose of this study was to determine the improvement of student learning outcomes by using the TGT model in grade IV elementary school students. The approach used is a qualitative approach to the type of classroom action research. The research was conducted in cycle I and cycle II which consisted of 2 meetings and consisted of 4 stages, namely planning, implementation, observation, and reflection. Data collection is done by observation, interviews, field notes, tests, and documentation. The results of this study indicate that the TGT model is well implemented so that the TGT model can improve student learning outcomes in cycle 1 with a percentage of 76% up to 97% in cycle 2.Â Hasil observasi di SDN Melis Kabupaten Trenggalek menunjukkan siswa kurang antusias dalam pembelajaran karena penggunaan model pembelajaran yang kurang menarik, dimana dari 17 siswa dinyatakan 11 belum tuntas, dan 6 tuntas. Tujuan penelitian ini untuk mengetahui peningkatan hasil belajar siswa dengan menggunakan model TGT pada siswa kelas IV Sekolah Dasar.Â Pendekatan yang digunakan pendekatan kualitatif dengan jenis penelitian tindakan kelas. Penelitian dilaksanakan dalam siklus I dan siklus II yang terdiri dari 2 pertemuan dan terdiri dari 4 tahap, yaitu perencanaan, pelaksanaan, observasi, dan refleksi. Pengumpulan data dilakukan dengan teknik observasi, wawancara, catatan lapangan, tes, dan dokumentasi. Hasil penelitian ini menunjukkan model TGT diterapkan dengan baik sehingga model TGT dapat meningkatkan hasil belajar siswa pada siklus 1 dengan prosentase 76% naik menjadi 97% pada siklus 2.